Toward Eve’s Exodus: Un-misrecognizing androcentric reproductive labor ideology in Christian right rhetoric and Genesis 1–3 - Freese, Elizabeth M. (Body and religion, 2022)
In an American context of reproductive injustice, the Christian right legitimizes a coercive pronatalist policy agenda by appeal to the theological belief that ‘human life begins at fertilization,’ which they ground in the biblical narrative of Genesis 1-3. Drawing upon interdisciplinary resources and utilizing an innovative feminist methodology, this article demonstrates that, while the story of pro/creation in Gen. 1-3 does not directly support ‘life at fertilization’ theology, it does provide a de facto undergirding for that conceptualization via its highly androcentric ideology of reproduction. Through symbolic, mythical narration of how ‘life’ comes to be, Gen. 1-3 constructs a central fiction of the Father God’s paternal reproductive omni-potence, which is built upon God’s colonization of agents with the capacity for maternal gestation labor and his violent destruction of those agents’ collective autonomy and capacity for reproductive anti-labor. In its ancient religious context, this rhetoric championed God’s patriarchal, patrilineal world-building project, which served those establishing and reinforcing a society that generated power and wealth for dominant men. As a story deeply socialized through lived religion over time, it operates now as a contemporary social fact that the Christian right exploits to construct its own, more extreme fiction of paternal omnipotence. Illumination of the Gen. 1-3 narrative’s oppressive constructions of women as reproductive laborers/anti-laborers - symbolized by Eve and other agents - enables feminist religio-cultural narrative intervention. A new story of life’s pro/creation is needed in both religious and secular settings to liberate ‘Eve’ and advance the movement for reproductive health, rights, and justice.